Manajemen Permainan Tradisional Megangsing di Desa Gobleg - Redi dana Yasa; Kadek Yogi Parta Lesmana; I Made Satyawan (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study is to describe the management of the traditional game megangsing, including planning, organizing, implementation, and monitoring in order to preserve local culture. The research method used is a qualitative approach with a descriptive method. Data collection was conducted through observation, in-depth interviews, and documentation analysis involving community leaders, megangsing participants, and residents of Gobleg Village. The results show that the management of the traditional game megangsing in Gobleg Village has been carried out quite well with support from traditional leaders, youth, and the community. However, aspects of documentation, promotion, and player regeneration still need to be improved to ensure the sustainability of this traditional game. In conclusion, the management of the traditional game megangsing in Gobleg Village has been implemented well, but requires improvements in documentation, promotion, and player regeneration to ensure sustainable cultural preservation and to serve as a reference for managing traditional games.   Keywords: Cultural Preservation, Gobleg Village, Management, Megangsing, Traditional Games